(untitled) (Research, Society and Development, 2021)
With the worsening of kidney failure over a long period of time, there is the development of uremic stomatitis in the oral cavity, a pathological process that has not been studied much and the number of clinical studies has been reduced. Objective: to evaluate the clinical-pathological aspects and methods of treatment and remission of uremic stomatitis through an integrative literature review. Methodology: This integrative literature review has a qualitative methodology, based on the development of the following research question: What are the main clinical and pathological aspects of uremic stomatitis? Three keywords were used to compose the research key, the following being (MeSH / DeCS): ((Uremic stomatitis)) AND (Anatomy OR Pathology, Oral). The eligibility criteria were as follows: articles that fit the theme; research involving anatomical and / or pathological aspects of uremic stomatitis; there were no restrictions on year and language. Results: Among the clinical aspects, we can mention the presence of whitish lesions on the back and side of the tongue, as well as white plaques distributed on the floor of the mouth, which may be associated with uremic breath and xerostomia in some cases. In addition to clinicians, an uremic stomatitis has some characteristic histological features: acanthosis with a superficially thick parakeratotic zone, a layer of deeply dilated keratinocytes, hyperplastic epithelium and unusual hyperparaceratinization. Thus, the diagnosis can be made based on the observation of clinical and histological aspects. Relief and complete remission of the pathological process are often achieved with targeted treatment for kidney disease, such as hemodialysis, for example. Conclusion: This integrative literature review included a detailed analysis of 6 articles and highlighted the clinical and pathological aspects of uremic stomatitis, including the most used treatment methods. The results obtained results successfully the guiding question of the research.